HUBUNGAN PATRON KLIEN ANTARA TAUKE DENGAN NELAYAN DI KEPENGHULUAN SUNGAI NYAMUK KECAMATAN SINABOI KABUPATEN ROKAN HILIR - Restu Lidya Ningsih; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at the fishermen village of Kepenghuluan Sungai Nyamuk Subdistrict Sinaboi Rokan Hilir Regency. The purpose of this research was to know how to shape social relationships economy and the factors that cause the attachment to patron clients between tauke with fishermen on Kepenghuluan Sungai Nyamuk, Subdistrict Sinaboi, Rokan Hilir Regency. The theory is theory of the Patron client expressed James C. Scott consists of the provision of services marketing, subsitensi crisis in the form of a Loan Guarantee, and provide assistance in the form of collective services. This type of research uses qualitative descriptive method with approach case studies. The subject of this research totalled 6 persons namely, 1 original tauke in villages that have been working for more than 5 years, and 5 in the village of fishermen who work a minimum of 5 years. A determination informants to use a technique purposive sampling. The data sources used are primary and secondary data sources. The data collected by the data collection techniques used observation and interview. The analysis of the data used in this research with the techniques of data collection from various sources with the place theory is used in accordance with the social phenomena. The results of this research is the patron-client relationships that need each other and so the relationship of interdependence remains the relationship attachment to each other either in the form of economic and social ties. factors cause attachment to social economic relations tauke (patron) fisherman (client) is the existence of a relationship of cooperation, solidarity and kinship relationships that will last due to a sense of comfort, protected and reticent. The formation of the patron-client relationship between tauke with fisherman Kepenghuluan Sungai Nyamuk in the background of relationship selling, debt receivable and give aid help misfortune, help of the highway, help a celebration of money, nine basic materials and power. Patron-client relationships that each other is intentionally created to meet the needs of life assurance.Keywords : Tauke (Patron), Fishermen (Client), A Client-Patron Relationship